Looking at the Link between Thinking Styles and Academic Achievement: The Case of One State Islamic University in Palembang - EKA SRI WARSITI (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2018)
The aims of this study were (1) to find out whether or not there was a significant correlation between each type of thinking styles and students’ academic achievement, (2) to identify if thinking styles significantly contributed to students’ academic achievement, and (3) to find out type of thinking styles becoming the best predictor for the academic achievement of one State Islamic University in Palembang. In this study, 460 EFL students of one State Islamic University in the academic year of 2016-2017 became the population of this study. 88 students were taken as samples by using purposive sampling method. The method used in this study was a correlational study. The data were obtained by using a ready-made questionnaire and documentation. Pearson Product Moment correlation coefficient and regression analysis of SPSS version 21.0 were used to analyze the obtained data. The results of the two analyses showed that (1) out of 13 types of thinking styles, only 9 types of thinking had positive and significant correlation to the students’ academic achievement; (2) those 9 types of thinking styles contributed to the students’ academic achievement with 48.8% contribution; and (3) hierarchical thinking style was the best predictor and contributed to the students’ academic achievement with 29.8% contribution.